High efficiency frequency doubling in fully diced LiNbO3 ridge waveguides on silicon. (14th July 2016) - Chauvet, Mathieu; Henrot, Fabien; Bassignot, Florent; Devaux, Fabrice; Gauthier-Manuel, Ludovic; Pêcheur, Vincent; Maillotte, Hervé; Dahmani, Brahim
Abstract: Nonlinear periodically poled ridge LiNbO3 waveguides have been fabricated on silicon substrates. Components are carved with only the use of a precision dicing machine without the need for grinding or polishing steps. They show efficient second harmonic generation at telecommunication wavelengths with normalized conversion reaching 204%/W in a 15 mm long device. The influence of the geometrical non uniformities of waveguides due to fabrication processes is asserted. Characteristics of the components are studied; notably their robustness and tunability versus temperature.